Evaluation of Robust Estimators Applied to Fluorescence Assays. (2008) - Västilä Västilä, M. M.; Peltonen Peltonen, S. S.; Soukka Soukka, J. J.; Albán Albán, E. E.; Soini Soini, J. T. J. T.; Ruotsalainen Ruotsalainen, U. U.
Abstract : We evaluated standard robust methods in the estimation of fluorescence signal in novel assays used for determining the biomolecule concentrations. The objective was to obtain an accurate and reliable estimate using as few observations as possible by decreasing the influence of outliers. We assumed the true signals to have Gaussian distribution, while no assumptions about the outliers were made. The experimental results showed that arithmetic mean performs poorly even with the modest deviations. Further, the robust methods, especially theM -estimators, performed extremely well. The results proved that the use of robust methods is advantageous in the estimation problems where noise and deviations are significant, such as in biological and medical applications.